Influence of the outside climate parameters on the selection of the optimum combination of the energy saving measures - Samarin, Oleg; Lushin, Kirill; Paulauskaitė, Sabina; Valančius, Kęstutis (Technological and Economic Development of Economy, 2009)
In this paper the influence of climatic parameters of building region on expedient depth of implementation of different ways of energy consumption decrease in civil buildings is reviewed. The data of multivariate calculations of power and technological efficiency of an adopted complex of energy saving measures for reference climatic zones of the terrain of Russia in modern economic conditions with allowance for discounting of costs are adduced. The analysis of the obtained outcomes is given and the guidelines are also offered at the choice of optimum combination of the solutions on a decrease of power inputs at exploitation of a building depending on the number of degree‐days of the heating season, as well as on established prices for stuffs both equipment and fares on power supplies. Klimato išorės parametrų įtaka optimaliam energiją taupančių priemonių deriniui Santrauka. Straipsnyje išnagrinėta statybos rajono klimato parametrų įtaka tikslingam įvairių energijos taupymo būdų taikymui visuomeninės paskirties pastatuose. Pateikiami energetinio ir techninio-ekonominio skirtingų energijos taupymo priemonių komplekso variantų, charakteringų Rusijos teritorijos klimato zonoms šiuolaikinėmis ekonominėms sąlygoms, įvertinant sąnaudų diskontavimą, skaičiavimo duomenys. Atlikta gautų rezultatų analizė ir pasiūlytos rekomendacijos, kaip pasirinkti optimalų energijos sąnaudų mažinimo derinį eksploatuojant pastatus, priklausomai nuo šildymo periodo dienolaipsnių ir galiojančių medžiagų, įrengimų ir šilumos tiekimo tarifų kainų. Reikšminiai žodžiai: energijos vartojimas, energijos taupymas, diskontuotas atsipirkimo laikas, šiluminė izoliacija, šilumos atgavimas, darni plėtra. First published online: 21 Oct 2010